Non-invasive chemical assessment of living human spermatozoa1. Issue 14 (19th February 2015) - Edengeiser, Eugen; Meister, Konrad; Bründermann, Erik; Büning, Steffen; Ebbinghaus, Simon; Havenith, Martina
<x xml:space="preserve">Abstract</x> Confocal Raman microspectroscopy was used to chemically image single and living human spermatozoa under near-physiological conditions.